A Reflection on Statistical Literacy and Curriculum Guidelines in Brazil for The Years of Elementary School - Baccar, Maria Helena (2022)
This work has been developed by the Fundão Project: Statistics and Probability, a collaborative project of the Federal University of Rio de Janeiro (UFRJ), composed of professors, undergraduate students and school level mathematics teachers. The research is part of a study whose focus is the teaching and learning of statistics and probability in elementary school. Our goal is the professional development of mathematics teachers. With attention to the initial phase of statistical literacy and based on an integrated approach, we considered the recent Brazilian normative orientations of Common National Curriculum Basis (BNCC) in Statistics and Probability to propose didactic sequences along the lines of the resolution of statistical investigation problems by the Guidelines for Assessment and Instruction in Statistics Education (GAISE).